Challenges & Suitability of TESL at the College Level in Bangladeshi Context - Hasan, Kamrul; Akhand, Mohd. Moniruzzaman (Journal of NELTA, 2010)
This paper presents the result of a study about teaching English to Bangladeshi college students. It analyses the problems faced by Bangladeshi English teachers, including methodological problems and expertise problem. The shifting from grammar based to communicative approach has produced acute problems of expertise in the field, resulting in inefficiency of the classroom instructors and lack of appropriate resources for language teaching. In response to the problems, this paper also discusses CLT methodology and considers the suitability of the Content-Based Approach (CBA) in Bangladeshi context. It then tries to uphold a balanced curricular and pedagogical suggestion for making language teaching more effective, arguing that blending of two approaches, CLT and CBA, can help English language teachers achieve maximum learning among students. Key Words: Communicative Language Teaching (CLT), Content-based Approach (CBA), Curriculum development DOI: 10.3126/nelta.v14i1.3090 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 45-54